Can Total Thyroidectomy Be Safely Performed by Residents?: A Comparative Retrospective Multicenter Study. Issue 14 (April 2016) - Gurrado, Angela; Bellantone, Rocco; Cavallaro, Giuseppe; Citton, Marilisa; Constantinides, Vasilis; Conzo, Giovanni; Di Meo, Giovanna; Docimo, Giovanni; Franco, Ilaria Fabiola; Iacobone, Maurizio; Lombardi, Celestino Pio; Materazzi, Gabriele; et al.
Abstract : Abstract: This retrospective comparative multicenter study aims to analyze the impact on patient outcomes of total thyroidectomy (TT) performed by resident surgeons (RS) with close supervision and assistance of attending surgeons (AS). All patients who underwent TT between 2009 and 2013 in 10 Units of endocrine surgery (8 in Italy, 1 in France, and 1 in UK) were evaluated. Demographic data, preoperative diagnosis, extension of goiter, type of surgical access, surgical approach, operative time, use and duration of drain, length of hospitalization, histology, and postoperative complications were recorded. Patients were divided into 3 groups: A, when treated by an AS assisted by an RS; B and C, when treated by a junior and a senior RS, respectively, assisted by an AS. The 8908 patients (mean age 51.1 ± 13.6 years), with 6602 (74.1%) females were enrolled. Group A counted 7092 (79.6%) patients, Group B 261 (2.9%) and Group C 1555 (17.5%). Operative time was significantly greater ( P < 0.001) in B (101.3 ± 43.0 min) vs A (71.8 ± 27.6 min) and C (81.2 ± 29.9 min). Duration of drain was significantly lower ( P < 0.001) in A (47.4 ± 13.2 h) vs C (56.4 ± 16.5 h), and in B (42.8 ± 14.9 h) vs A and C. Length of hospitalization was significantly longer ( P < 0.001) in C (3.8 ± 1.8 days) vs B (2.4 ± 1.0 days) and A (2.6 ± 1.5 days). No mortality occurred. Overall postoperative morbidity was 22.3%: it was significantly higher in B vs A (29.5% vs 22.3%; odds ratio [OR] 1.46, 95% confidence interval [CI] 1.11–1.92, P = 0.006) and C (21.3%; OR 1.55, 95% CI 1.15–2.07, P = 0.003). No differences were found for recurrent laryngeal nerve palsy, hypoparathyroidism, hemorrhage, and wound infection. The adjusted ORs in multivariate analysis showed that overall morbidity remained significantly associated with Group B vs A (OR 1.48, 95% CI 1.12–1.96, P = 0.005) and vs C (OR 1.60, 95% CI 1.19–2.17, P = 0.002), while no difference was observed in Group A vs B + C. TT can be safely performed by residents correctly supervised. Innovative gradual training in dedicated high-volume hospitals should be proposed in order to allow adequate autonomy for the RS and safeguard patient outcome.